Exploring STEM education trends in Malaysia: Building a talent pool for Industrial Revolution 4.0 and Society 5.0 - Rashidin Idris; Juppri Bacotang (Human Resource Management Academic Research Society, 2023)
In Malaysia, Science, Technology, Engineering, and Mathematics (STEM) education is becoming increasingly important in the current industrial revolution 4.0 and society 5.0 era. This study aims to investigate the current STEM education trends in Malaysia, the benefits of pursuing STEM careers in the future, and the need to build a talent pool to meet the demand of these two revolutions. This study highlights the various STEM education trends in Malaysia, including the incorporation of STEM-related subjects in the national curriculum and the promotion of STEM-related extracurricular activities. It also discusses the benefits of pursuing a career in STEM, such as higher earning potential and job security, as well as the importance of preparing a talent pool to meet the demand of the rapidly changing technological landscape. This study argues that Malaysia needs to focus on developing a robust STEM education system that can produce a workforce equipped with the necessary skills and knowledge to excel in the industries of the future. The study also highlights the role of policy makers, researchers, and educators in this process and proposes recommendations for enhancing STEM education in Malaysia. This study contributes to the literature on STEM education in Malaysia and provides valuable insights for policy makers, researchers, and educators.